Management of logistics transport flows of the enterprise - Wei, Ben (Харківський національний автомобільно-дорожній університет, 2024)
The paper is relevant due to the significant interest in this topic in modern science and the insufficient level of its theoretical and methodological development. Consideration of issues related to this topic is of both theoretical and practical importance, since no organization can exist without transportation in our time, but despite this, transport logistics remains not fully studied. The most underdeveloped and not fully researched aspect of transport logistics is the management of logistics traffic flows. The paper investigates the theoretical foundations of logistics transport flow management; analyzes the current system of enterprise transport flow management; develops a methodology for evaluating the system of enterprise logistics transport flow management; develops an action plan for optimizing vehicle routes; calculates the economic efficiency of the proposed measures.
Keywords: management; hr-analytics; enterprise personnel; motivation; personnel management system